PENGARUH BAURAN PROMOSI TERHADAP KEPUTUSAN PEMBELIAN PADA PT XL AXIATA TBK DI KOTA PALEMBANG - Yuni Adinda Putri; Sulbahri Madjir (Politeknik Ubaya, 2022)
The competition of cellular operators in fighting over consumers in order to maintain market share will be expected to occur continuously in the future. In the era of globalization, many new industries have emerged, but many companies have closed. Therefore, to maintain its existence the company must have good marketing. Marketing is the most important factor to increase product sales. One of the strategies is to carry out promotional activities for their products. This mix is ​​the most appropriate way according to management will meet the needs of the target market as a whole. The promotion mix includes, advertising, personal selling, sales promotion, public relations, and direct marketing. The purpose of the study was to determine the effect of the promotion mix variable on purchasing decisions at PT XL Axiata Tbk in Palembang City. The method used is a quantitative method. Data collection was carried out by non-probability sampling technique with sampling technique, namely incidental sampling. The results obtained that the most dominant independent variable influencing the decision to use the XL card (Y) in the city of Palembang is the sales promotion variable (X3) seen by the largest regression coefficient value.